ENHANCING LEARNING IN THE DIGITAL AGE: A STUDY OF BLENDED TEACHING REFORM FOR COLLEGE STUDENTS - Sophia , Martinez; Diego, Lopez (Top Educational Review Journal (TERJ), 2024)
In recent years, Chinese universities have made significant strides in enhancing teaching quality. However, several issues have emerged, including a focus on knowledge transmission over nurturing students’ autonomous learning skills and a deficiency in comprehensive student assessment and evaluation. To address these challenges, universities have embarked on a series of reforms to traditional teaching models. As network technology becomes more pervasive, universities are embracing the concept of blended teaching. This approach does not entirely replace traditional methods with technology but integrates network technology into conventional teaching to leverage complementary strengths. Many institutions are actively exploring and implementing blended teaching, yet numerous aspects of this teaching model warrant further investigation. This includes the integration of the flipped classroom concept with traditional teaching, the effective design and development of blended courses, and other aspects that offer ample opportunities for in-depth study and exploration.